1995
DOI: 10.1139/v95-200
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of squaraine dyes: Structure–property relationships and solvent effects

Abstract: Abstract:In characterizing the UV-visible absorption properties of a series of seven anilino class squaraine dyes in dimethyl sulfoxide (DMSO) -water mixtures, spectral features characteristic of aggregation were observed. These included hypsochromic and hypochromic shifts of the absorption maximum, relative to the nonassociated state of these dyes. Previously aggregation of this class of squaraine dyes had only been reported in studies of Langmuir-Blodgett (LB) films prepared with squaraine dyes. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 19 publications
5
37
0
3
Order By: Relevance
“…The obtained computational effects of aggregation on the absorption spectrum comply well with the aggregation manifestation in the experiment: the signal shift and broadening [11,[18][19][20].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The obtained computational effects of aggregation on the absorption spectrum comply well with the aggregation manifestation in the experiment: the signal shift and broadening [11,[18][19][20].…”
Section: Discussionsupporting
confidence: 79%
“…A thorough investigation of squaraines in various media has revealed that they can form either H-or J-aggregates depending on their structure and parameters of microenvironment [11,18,19]. Moreover, the given squaraine dye can be forced into the H-or J-aggregates by the proper choice of material preparation conditions.…”
mentioning
confidence: 99%
“…All the studied squaraines showed excellent emission properties in organic solvents but a poor emission when PBS buffer amount increased due to an aggregation caused quenching (ACQ) effect (Figure ). Actually, it is well known and deeply described in literature that, when the squaraine alone is in a water solution, it tends to form non‐fluorescent aggregates . One of these squaraines, that is, VG1‐C8, already showed, in solid state, micron‐sized polycrystalline aggregate exhibiting a large Stokes shift (322 nm) .…”
Section: Resultsmentioning
confidence: 99%
“…To optimize the performance, controlling the conformation is a critical issue for applications based on these materials. Preceding workers have investigated the variation of the structural conformation for squaraine-based materials through solvent concentration [23,24], solvent polarity [23,[25][26][27], temperature [23,28], metal ions [29][30][31] and other conditions. Besides induction by these external stimuli, other techniques might control the conformation of polysquaraine.…”
Section: Introductionmentioning
confidence: 99%